Increasing pro-environmental behavior in the home and work contexts through cognitive dissonance and autonomy - Bentler, Dominik; Kadi, Gizem; Maier, Günter W. (Frontiers in Psychology, 2023)
The aim of this study was to develop a novel cognitive dissonance intervention founded on the action-based model for enhancing pro-environmental behavior. Based on intraindividual feedback on the expression of personal pro-environmental attitudes and behavior the study confirms the effect of cognitive dissonance intervention to foster pro-environmental behavior. The effect of this intervention could be demonstrated for the home as well as for the work context, although the effects for the work domain were lower. This can be explained by specific situational conditions of the work domain. Autonomy for pro-environmental behavior is significantly lower in the work context than in the home context and significantly moderates the effect of the cognitive dissonance intervention. The present work provides information on how pro-environmental behavior can be influenced in different contexts as well as the significance of situational framework conditions for the effect of behavior-changing interventions.